Determinants for choosing and adhering to active surveillance for localised prostate cancer: a nationwide population-based study. Issue 12 (23rd December 2019) - Bergengren, Oskar; Garmo, Hans; Bratt, Ola; Holmberg, Lars; Johansson, Eva; Bill-Axelson, Anna
Abstract : Objective: Knowledge about factors influencing choice of and adherence to active surveillance (AS) for prostate cancer (PC) is scarce. We aim to identify which factors most affected choosing and adhering to AS and to quantify their relative importance. Design, setting and participants: In 2015, we sent a questionnaire to all Swedish men aged ≤70 years registered in the National Prostate Cancer Register of Sweden who were diagnosed in 2008 with low-risk PC and had undergone prostatectomy, radiotherapy or started on AS. Outcome measurements and statistical analysis: Logistic regression was used to calculate ORs with 95% CIs for factors potentially affecting choice and adherence to AS. Results: 1288 out of 1720 men (75%) responded, 451 (35%) chose AS and 837 (65%) underwent curative treatment. Of those starting on AS, 238 (53%) diverted to treatment within 7 years. Most men (83%) choose AS because 'My doctor recommended AS'. Factors associated with choosing AS over treatment were older age (OR 1.81, 95% CI 1.29 to 2.54), a Charlson Comorbidity Index >2 (OR 1.50, 95% CI 1.06 to 2.13), being unaccompanied when notified of the cancer diagnosis (OR 1.45, 95% CI 1.11 to 1.89). Men with a higher prostate-specific antigen (PSA) at the time of diagnosis were less likely to adhere to AS (OR 0.26, 95% CI 0.10 to 0.63). The reason for having treatment after initial AS was 'the PSA level was rising' in 55% and biopsy findings in 36%. Conclusions: A doctor's recommendation strongly affects which treatment is chosen for men with low-risk PC. Rising PSA values were the main factor for initiating treatment for men on AS. These findings need be considered by healthcare providers who wish to increase the uptake of and adherence to AS.